AWARENESS OF VARIOUS WEB PORTALS AMONG LIBRARIANS WORKING IN THE CBSE SCHOOLS OF MAHARASHTRA - Vinita Sarman Yadav; Dr. Ashokkumar S. Khobaragade (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The digital revolution in the education sector has altered the role of school librarians to be more than bookkeepers but facilitators of digital literacy and information fluency. In the CBSE school curriculum of Maharashtra, librarians are supposed to play an active role in intertwining different pedagogical web portals, i.e., the National Digital Library (NDL), e-PG Pathshala, DIKSHA, and SWAYAM, into the teaching-learning process. Nonetheless, the level of this portal awareness and usage is not clear. The given study explores the level of awareness of the digital portals among the librarians in the CBSE schools of Maharashtra and presents the problem of closing the digital divide and providing students with equal access to digital resources. The study arose as the adoption of a descriptive research design, inclusive of a cross-sectional survey of 640 teachers and 320 librarians picked proportionally across the six revenue divisions of Maharashtra. Data collection utilised well-structured research instruments, was analysed using SPSS 18.0, and employed descriptive statistics and inferential tests at a 5 percent significance level. The results of the study indicate that there are essential gaps in their knowledge and usability of important web portals, which may indicate a low level of use of valuable resources in academics and government. This highlights the pressing importance of specific professional development and training on digital literacy among librarians in order to enable them to be instructional collaborators in schools. The research is relevant because it raises awareness among CBSE school librarians in Maharashtra about navigating the digital era and offers suggestions for policy interventions and training models that could enhance the effective use of digital portals. The research contributes to the awareness of librarians of the possibility of improving the outcomes of student learning and developing equitable digital education in the state.